MODELUL EXPERIMENTAL DE FORMARE A COMPETENŢEI DE COMUNICARE ASERTIVĂ LA STUDENŢII DIN MEDIUL ACADEMIC MULTIETNIC - USM ADMIN (Moldova State University, 2011)
This article describes the pedagogical model of assertive communication competence development of students, representatives of various multiethnic groups. The model reflects the social conditions, objectives, stages, levels, conditions for the formation of assertive communication competence. We propose pedagogical technologies of formation of the specified competence.